Vietnam : Transition to a Market Economy - Srinivasan, Krishna (Occasional Papers; Occasional Paper ;, 1996)
The paper explores the pattern of transition of the Vietnamese economy, the policies that were applied, and the reasons for the country's success. In particular, it focuses on output performance; state-owned enterprises; foreign direct investment; determinants of inflation; dollarization and problems of economic management; international integration and exchange rate policy; growth and diversification of trade, trade reform, exchange reform, and exchange rate policy.